The current status of nurses-doctors collaboration in clinical decision and its outcome in Tanzania - Joanes Faustine Mboineki; Changying Chen; Dolla Deo Gerald; Cecilia Amponsem Boateng (Wiley, 2019)
Abstract Aim The aim of this study was to establish the current level of collaboration between nurses and medical doctors (MDs) in the making of clinical decisions. Design Descriptive qualitative design was applied in this study. Methods Semi‐structured interviews were conducted to collect qualitative data. Contents were arranged according to their similarities, whereas content analysis was used to identify explanatory themes. Results Nurses feel disrespected when medical doctors (MDs) ignore their opinions. The impression of lower level of education of nurses is seen as a cause to their opinions been ignored by the medical doctors. Nurses sometimes adhere to the instructions of MDs, but on other times, they carry on with their own proposed treatment. Implications for nursing practices Involvement of nurses in clinical decisions will enable nurses to effectively advocate for patients.